Studies in Australian Tettigoniidae: A review of the Australian katydids of the genus Goodangarkia (Tettigoniidae: Conocephalinae; Agraeciini; Liarina) - Rentz, Dcf; Su, You Ning; Ueshima, Norihiro; Wilson, Gw (Zootaxa, 2016)
Six species in Goodangarkia are described. Information on the distribution. ecology and cytology of species is presented. An unusual characteristic of cranial stridulation of one species is noted. Cytological evidence suggests the chromosome complement of species are more basal than those from Africa for example.